Persepsi Pengaturan Sound System pada Pertunjukan Campursari Ringkes di Nogosari, Boyolali - Wibowo, Triyan Adi (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
A sound system operator at a wedding celebration in Nogosari, Boyolali, has his own perception in addressing the sound management. One of the operators in this area is Dardi. Neither coming from a family of musicians not having academic background in the field of sound engineering, Dardi is capable of operating the sound system to satisfy his listeners with his performance. As a sound system regulator, Dardi has served sound system service providers at celebrations with puppet shows, dangdut, rebana, and campursari. Each performance is carried out with a different setup. Among the differing setups, Dardi is more competent in the setup of campursari shows. Based on the Dardi’s perceptions on sound system regulation, the author is interested in studying the perception of the sound system operator in the sound of campursari music? Based on the findings from the analysis of Dardi's perception as the sound system operator, there are many considerations and adaptations to different places of performance. He initially practiced in the field without being equipped with theory or science, that he tried his best to be approved by following his brother’s workflow. Through this process, he slowly learned and perfected his own amplification setup. His habit of listening to the sounds of various musical instruments also helps sharpen his musical sensitivity. The awareness that was built by Dardi was through empirical experience and instinct for the sounds he heard. This makes his sound system settings always changes instead of being fixed.